Usage of English language materials from the internet to improve students English language performance / Saripah Anak Sinas - Sinas, Saripah (2013)
This study investigated the factors that motivate students to read English Language materials from the Internet, the types of materials from the Internet that motivate students to read and how English Language reading materials from the Internet contribute to students’ language performance. A total number of 80 students from Semesters One and Two from MARA Skills Institute (IKMK) were involved in the study. A total of eighty sets of questionnaire were distributed for feedback or responses. Besides that, Pre-test and Post-test were conducted with the samples to determine the students’ improvement in their language performance. The data was analysed descriptively. Findings of the study illustrated that among the factors which motivate students to read English Language materials from the Internet are self-motivation, self-interest, and encouragement from their teachers to use the Internet as a tool to search for materials. The findings revealed that the types of materials the students read were biographies, articles, journals, e-books, e-magazines, e-newspapers and also join social websites via face-book, video conferencing and emails. As a result, the finding of the study showed that students’ language test performance has slightly improved in the Post-test as compared to the Pre-test. The present study is relevant as it provides knowledge and information for students and teachers that English Language materials from the Internet can be used to encourage and motivate students to read and enrich their vocabularies of the target language. As for the implication, it is vital for the students to nurture positive attitude and interest towards reading the English Language materials from the Internet to help improve their language performance.